A guide to Zona pellucida domain proteins - Wassarman, Paul M.; Litscher, Eveline (Hoboken, New Jersey : Wiley, 2015)
This book provides a coherent, clear, and uniform presentation of structural, genetic, molecular, and biochemical information available for the zona pellucida domain protein family, which impact pathologies such as infertility, deafness, and cancer. Furthermore it: -Details information about the structure and function of the ZP domain in ZPDC-proteins -Provides illustrations of the organization of ZPDC-proteins, the genes that encode the proteins, and examples of mutations in the ZP domain that cause diseases -Speculates as to the evolution of the ZP domain and potential therapeutics for diseases stemming from ZP domain mutations -Addresses mammalian and non-mammalian systems.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Zona pellucida; Cell receptors -- Physiology; SCIENCE / Life Sciences / Anatomy & Physiology; Zona Pellucida -- physiology; Egg Proteins -- physiology; Membrane Glycoproteins -- physiology; Receptors, Cell Surface -- physiology; Electronic books; Electronic books